Calculational model for first-mode eigenfrequency of a semi-guy-wired vertical-axis wind turbine tower. Issue 2 (April 2021) - Möllerström, Erik; Ottermo, Fredric
A simple model for accounting for tower mass when estimating the first-mode eigenfrequency of a semi-guy-wired tower has been derived. This extends previous work where an analytical model of the semi-guy-wired tower of a 200-kW vertical-axis wind turbine was developed. The model was primarily used to estimate the eigenfrequencies as a result of adding guy wires to a free-standing tower (thus creating a semi-guy-wired setup). However, a weakness with the model was that the tower mass was accounted for in a rough way that essentially ignored the guy wires, which gave a larger-than-necessary error. In this work, an effective top mass, that takes into account the tower mass and the constraints from the guy wires, is derived to achieve a higher accuracy when estimating the first-mode eigenfrequency. This, together with the earlier models, gives a more complete method to estimate the eigenfrequencies for a semi-guy-wired wind turbine.